Simulation and Realization of MPPT methods in photovoltaic system - سويد, صابر; نيني, ادريس; مشري, صلاح الدين (Université d'El Oued, 2021)
"Photovoltaic energy (PV) is increasingly gaining its place in alternative energy sources but solar panels, despite the development in manufacturing technologies, suffer from a fairly low energy conversion efficiency, this efficiency can be even lower if the photovoltaic generator (PVG) does not work around a point called: maximum power point MPP. The pursuit of this point, which changes position with climatic conditions, is a very important step in the design of a PV system. In this thesis we are going to simulation, optimization and realization of a photovoltaic system operating with a booster converter. This study covers the implementation of different algorithms of the maximum power point such as by the perturbation and observation algorithm (P&O), Incremental conductance (InC) , Fuzzy logic and PSO-PID .Therefore, we will start with the simulation and modeling of the photovoltaic cell and the boost converter according to the mathematical model. Then, we have detailed several MPPT algorithms controlling our converter. Finally, we have design and implementation of our system with the two MPPT algorithms based on an Arduino Mega 2560 board" "تكتسب الطاقة الكهروضوئية )PV )ماكنهتا بشلك مزتايد يف مصادر الطاقة البديةل ، لكن ا أللواح الشمس ية ، عىل الرمغ من التطور يف تقنيات التصنيع ، تعاين من كفاءة حتويل طاقة منخفضة اىل حد ما ، وميكن أأن تكون هذه الكفاءة أأقل اذا مل يعمل املودل الكهروضويئ )PVG )حول نقطة تسمى: نقطة الطاقة القصوى MPP .يعد السعي وراء هذه النقطة ، اليت تغري املوقع مع الظروف املناخية ، خطوة هممة للغاية يف تصممي نظام الكهروضوئية. س نقوم يف هذه ا ألطروحة مبحااكة وحتسني وحتقيق نظام فلطايئ ضويئ يعمل مبحول معزز. تغطي هذه ادلراسة تنفيذ خوار زميات خمتلفة ألقىص نقطة للطاقة مثل خوارزمية الاضطراب واملراقبة )O&P ، )والتوصيل ا لضايف )InC ، )واملنطق . بعد ذكل ، لل الراييض الضبايب و PID-PSO ، ذلكل سنبدأأ مبحااكة ومنذجة اخللية الضوئية وحمول التعزيز وفقًا منوذج مقنا بتفصيل العديد من خوارزميات MPPT اليت تتحمك يف احملول اخلاص بنا. أأخ ًريا ، دلينا تصممي وتنفيذ نظامنا ابس تخدام خوارزميتني MPPT استناًدا اىل لوحة 2560 Mega Arduino."
RESEAUX ELECTRIQUESمذكرة ماستر تخصص
Keywords: "Photovoltaic generator, MPP, booster, P&O, INC, Fuzzy logic, PSO-PID, Simulation, Implementation , MPPT, Arduino Mega."; "ودل الطاقة الكهروضوئية ، MPP ، ادلامع ، O&P ،INC ، املنطق الضبايب ، PID-PSO .Arduino Mega ،MPPT ، التنفيذ ، احملااكة،"